Vision 2020 – where we went wrong - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
WE should have been jubilantly welcoming a “2020 Malaysia” based on Wawasan 2020 that was launched in 1991. It was a powerful rallying point in the drive to push Malaysia out of the middle-income trap and to be a “developed” country. But the timeline has now been extended to 2030 and another strategy adopted – the “Shared Prosperity Vision (SPV)”. There are many reasons for this, notably, the state of affairs that the country is in on several fronts: economically, ecologically and socially. Most telling is the last of the three, gauged by the nine challenges that make up the Wawasan. Out of the nine, five have fallen short in meeting the well defined targets. For example, the first challenge is the creation of Bangsa Malaysia. Yet we are worse off than in 1991. So, too, the other four which could also be categorised as values-based from the socio-cultural perspective. Including those that border on issues of ethics and morality. Be it the creation of a caring and loving Malaysian community or that of a just and equitable Malaysia. The fact that SPV has been introduced, somewhat signals the misalignment to the goals set for a more egalitarian Malaysia. Meaning, today the harmonious balance between the three dimensions of economic-ecological-societal is still wanting. Evidence of these abound, leading to the pronouncement of the SPV 2030.